Inclusion byproduct of Chía (Salvia hispanica L.) in the ration of dairy cows and its effect on milk production and composition. Technical note - Criscioni, Patricia; Ferreira, Néstor; Páez, Marcos; Lara, Marta; Peralta, José; Paz–Corrales, María; Gauna, Lidia (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
Some by–products can be used in animal feeding depending on their nutritional characteristics, with respect to this, Chía by–product have not been well investigated. The objective of this experiment was to study the inclusion of Chía by–products (Salvia hispanica L.) in the ration of dairy cows and its effect on the performance productive and milk composition. Ten Holstein cows in the first third of lactation, PV 500 ± 50 kg were selected, were assigned to 2 treatments in a crossover design, where each cows received both treatments in 2 periods. One group was fed with inclusion of Chía cake in the ration (Diet 1) and the other without inclusion of Chía cake in the ration (Diet 2). Diets were formulated to be isoenergetic. The animals were kept under the same sanitation and management conditions, with two daily milkings, in the morning and afternoon. After 12 days of adaptation to the diet, and during a 5–day measurement period, feed intake and individual milk production were recorded daily, and samples were taken to determine the chemical composition. Milk production was difference for both diets (P<0.05); Diet 1: 27.34 ± 3.28 L vs 28.85 ± 2.46L for Diet 2. Chemical composition of the milk, showed significant differences in crude protein (3.02 ± 0.21 and 3.25 ± 0.1 %), and not fat solids (8.5 ± 1.24 y 8.98 ± 0.28 %); for the fatty acids detected differences were not significant (P<0.05). Differences were observed between both diets in some parameters; probably because of the lipid content in Diet 1.